2015
DOI: 10.1136/annrheumdis-2014-206737
|View full text |Cite
|
Sign up to set email alerts
|

Lower education and living in countries with lower wealth are associated with higher disease activity in rheumatoid arthritis: results from the multinational COMORA study

Abstract: Female gender and lower individual or country SES were independently associated with DAS28, but did not reinforce each other. The association between lower individual SES (education) or lower country welfare (GDP) with higher DAS28 was partially mediated by uptake of bDMARDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 20 publications
5
56
1
1
Order By: Relevance
“…But reality is more complicated. The effectiveness of bDMARD-usage in countries’ all-day clinical practice may be overstated: previous research estimated that ‘only’ 7% of the effect of GDP per capita on DAS28 was mediated by the uptake of bDMARDs 4. We found ‘only’ 2.8% more patients in DAS28-remission for every additional 10% patients using a bDMARD.…”
Section: Discussionmentioning
confidence: 57%
“…But reality is more complicated. The effectiveness of bDMARD-usage in countries’ all-day clinical practice may be overstated: previous research estimated that ‘only’ 7% of the effect of GDP per capita on DAS28 was mediated by the uptake of bDMARDs 4. We found ‘only’ 2.8% more patients in DAS28-remission for every additional 10% patients using a bDMARD.…”
Section: Discussionmentioning
confidence: 57%
“…7 In fact, several studies have shown that living in countries with higher wealth is associated with lower RA disease activity. [13][14][15] This might be due, in part, to differences in types of concomitant therapies used, but the results from the global GO-MORE population did not reveal an effect of DMARD type or concomitant corticosteroid use on RA disease activity. 8 Better quality of care might also lead to higher patient expectations and therefore better responses to treatment.…”
Section: Fundingcontrasting
confidence: 48%
“…Este hallazgo se corroboró con los reportes que muestran una prevalencia alta en el género femenino, asociada con las características hormonales y genéticas propias de la mujer, las cuales hacen que las enfermedades autoinmunes sean más frecuentes en ellas (22)(23)(24).…”
Section: Discussionunclassified